The Influence of Graduate's Employability Skills Towards Management's Perception: Case of PT Bank Rakyat Indonesia (BRI) TBK Medan, Indonesia - Siregar, Novient Nur'arif (2011)
More than 14 million of Indonesian unemployed university graduates are out of work for more than six to one year. This caused by they cannot compete with other graduates and not fulfill employer’s requirements of employability skills or known as non-technical skills of graduates. Graduates more concern of their technical skills and excellent result that it would be supports your non-technical skills. Besides that, this is also become suggestion through universities need to do more in improvement of graduate’s chances in the labour market and trained them to develop their skills so that they can handle graduate’s unemployment issues. The purpose of this study is to identify six dimensions of graduate’s employability skills towards management’s perceptions in PT Bank Rakyat Indonesia (BRI) Tbk. To attain the objective of this study, a quantitative method was employed and data were collected through questionnaire. The questionnaire was adapt from Mohd Yusof Husain, Seri Bunian Mokhtar, Abdul Aziz Ahmad, and Ramlee Mustapha (2010) regarding the importance of employability skills and Azami Zaharim, Yuzainee Md Yusoff, Mohd. Zaidi Omar, Azah Mohamed, Norhamidi Muhamad and Ramli Mustapha (2009) for employer’s perception. A total of 60 questionnaires were distributed to the all management level of PT Bank Rakyat Indonesia (BRI) Tbk., and perfectly received 60 (100%) used for analysis. Mean, standard deviation, Pearson correlation coefficient and linear regression were used to achieve objective the study. The result from mean analysis show that management’s perception levels on employability skills are high for all dimensions, where the mean was above 4.00. Pearson Correlation Coefficient shows that the basic skill has stronger relationship with management’s perceptions (r ≤ .620; p < 0.05). Linear regression analysis shows that only the basic skill (β ≤ .404; p < 0.05) was influence to the management’s perceptions in PT. Bank Rakyat Indonesia (BRI) Tbk. Medan, Indonesia. This study suggest that graduates must look back at their soft skills and follow what management’s requirements so that they can prepared it before they enter job market. Besides that, the universities as higher institution and employers should work together in terms of develop graduates skills and decides what major things that job market looking for from graduates for now and future.